Elevated temperature material properties of a new high-chromium austenitic stainless steel - Liang, Yating (2020)
A testing programme was conducted to investigate the material properties of a new high-chromium grade of austenitic stainless steel - EN 1.4420 at elevated temperatures. A total of 164 tensile coupons extracted from both cold-rolled and hot-rolled sheets were tested; 80 coupons were tested isothermally with temperatures ranging from 25 °C to 1100 °C, and 84 were tested anisothermally with stress levels ranging from 10% to 90% of the material 0.2% proof stress at room temperature. The experimentally derived reduction factors for the key material properties were compared with existing design values. Design recommendations for the elevated temperature reduction factors were then proposed for this new grade, and a two-stage Ramberg–Osgood model was shown to be able to accurately represent the material stress–strain response at elevated temperature.